2008
DOI: 10.1182/blood-2007-09-111773
|View full text |Cite
|
Sign up to set email alerts
|

Kpm/Lats2 is linked to chemosensitivity of leukemic cells through the stabilization of p73

Abstract: Down-regulation of the Kpm/Lats2 tumor suppressor is observed in various malignancies and associated with poor prognosis in acute lymphoblastic leukemia. We documented that Kpm/Lats2 was markedly decreased in several leukemias that were highly resistant to conventional chemotherapy. Silencing of Kpm/Lats2 expression in leukemic cells did not change the rate of cell growth but rendered the cells more resistant to DNA damageinducing agents. Expression of p21 and IntroductionThe Warts (Wts) tumor suppressor gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 82 publications
5
41
0
1
Order By: Relevance
“…In our previous study, we also reported YAP amplification in a subset of MM cells (28). Regarding LATS2, downregulation of LATS2 was reported to be correlated with poor prognosis of leukemia (42) and missense mutation was also reported in lung cancer (43). However, null status of LATS2 such as by homozygous deletion or nonsense mutation was not reported in these malignancies.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous study, we also reported YAP amplification in a subset of MM cells (28). Regarding LATS2, downregulation of LATS2 was reported to be correlated with poor prognosis of leukemia (42) and missense mutation was also reported in lung cancer (43). However, null status of LATS2 such as by homozygous deletion or nonsense mutation was not reported in these malignancies.…”
Section: Discussionmentioning
confidence: 94%
“…Firstly, loss of LATS2 was associated with resistance to two chemotherapeutic drugs, doxorubicin or etoposide, in leukemogenic cells. 69 And secondly, simultaneous loss of both LATS1 and LATS2 renders HeLa cells more resistant to the microtubule-damaging drug Taxol. 72 These studies allude to the potential predictive value of LATS in determining treatment outcomes.…”
Section: Functions Of Latsmentioning
confidence: 99%
“…Firstly, in acute lymphoblastic leukemia, it was shown that expression of LATS2 was the most important prognostic factor in predicting both disease-free survival and overall survival when surveying potential prognostic factors. 3 In addition, loss of LATS2 leads to decreased sensitivity to two commonly used chemotherapeutic drugs, doxorubicin and etoposide, in leukemic cell lines, 69 suggesting that expression of LATS2 might also serve as a valuable predictive factor.…”
Section: Role Of Lats As Tumor Suppressormentioning
confidence: 99%
“…12 The biological effect of Hpo signaling is likely to be context dependent, and there is evidence that Yap can promote cell death by binding to a p53 family member, p73. 77,78 In Drosophila, Hpo pathway components also play roles in other developmental processes including retina cell patterning, 79 dendrite morphogenesis, 80,81 regulation of oocyte polarity [82][83][84] and salivary gland degeneration. 85 Furthermore, Hpo signaling regulates salivary gland cell death in a PI3K-dependent, but Yki-independent, manner.…”
Section: How Does the Hpo Pathway Read The Spatial And Temporal Signals?mentioning
confidence: 99%